Utilization of Waste Oil Capsules for Self-Healing Hot Mix Asphalt: A Sustainable Approach - Cetinkaya, Sena; Yalcin, Erkut; Yilmaz, Mehmet (Springer Heidelberg, 2026)
An inventive technique to lessen asphalt pavement cracking is the addition of capsules to hot mix asphalt (HMA). This process, called self-healing, makes asphalt mixtures more durable. This study examines how the fatigue resistance and self-healing capabilities of HMA specimens are affected by customized capsules that contain waste mineral oil and waste vegetable oil as curatives. In this investigation, four distinct ratios of polymeric capsules 0.25%, 0.50%, 0.75%, and 1.0% that had been adjusted in earlier studies were added to HMA specimens. Using machine learning-based image analysis of core asphalt samples, their spatial distribution inside the asphalt mixtures was assessed as an alternative to CT scans. The main conclusions of this study are as follows: (1) The capsules in the HMA specimens have a tendency to cluster as the percentage of capsules in the asphalt mixture rises. (2) The use of capsules improves crack healing and extends the fatigue life of damaged specimens, according to the findings of 4-point bending fatigue testing. Furthermore, waste mineral oil-containing capsules performed better than waste vegetable oil-containing capsules. (3) Although there were minor impacts on several of the mechanical and physical characteristics of HMA, the self-healing ability improved as the percentage of capsules in HMA specimens rose.
Keywords: Hot mix asphalt; Fatigue; Waste vegetable oil; Waste mineral oil; Self-healing; 4-point bending